1962
DOI: 10.1111/j.2042-7158.1962.tb11139.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Screening of Some West Indian Medicinal Plants

Abstract: A systematic pharmacological examination has been made of 55 Jamaican plants, most of which have a local reputation as medicinals. A number of interesting, but no outstanding, activities were observed. The results are tabulated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
24
0
2

Year Published

1966
1966
2015
2015

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(27 citation statements)
references
References 1 publication
0
24
0
2
Order By: Relevance
“…Estudos realizados com algumas espécies de Turnera têm revelado várias atividades biológicas, dentre as quais destacam-se as atividades: antimutagênica (Wall et al, 1988), antihiperglicêmica (Alarcon-Aguilara et al,1998), afrodisíaca (Arletti et al, 1999), antiulcerativa (Gracioso et al, 2000), hipotensiva (Vieira et al, 1968), antiinfl amatória (Antonio;Souza 1998), larvicida (Kalyanasudaram;Diaz 1985), antimalárica (Antoun et al, 2001), espasmogênica e também vasodilatadora (Feng et al, 1962).…”
unclassified
“…Estudos realizados com algumas espécies de Turnera têm revelado várias atividades biológicas, dentre as quais destacam-se as atividades: antimutagênica (Wall et al, 1988), antihiperglicêmica (Alarcon-Aguilara et al,1998), afrodisíaca (Arletti et al, 1999), antiulcerativa (Gracioso et al, 2000), hipotensiva (Vieira et al, 1968), antiinfl amatória (Antonio;Souza 1998), larvicida (Kalyanasudaram;Diaz 1985), antimalárica (Antoun et al, 2001), espasmogênica e também vasodilatadora (Feng et al, 1962).…”
unclassified
“…In Jamaica, the tea of leaves is used by women against painful menstruation (Asprey & Thornton, 1955). The leaves and the stems have spasmolytic activity on guinea pig ileum as well as on rabbit duodenum, and also was confirmed the vasodilator activity on isolated rats' hindquarter (Feng et al, 1962).…”
Section: Introductionmentioning
confidence: 72%
“…It produces a fruit called soursop due to its slight acidic taste when ripe. Annona muricata trees also called graviola (common name) are native to the Caribbean and Central America but now are widely cultivated in tropical climates throughout the world [6]. Available scientific evidence revealed that A .…”
Section: Introductionmentioning
confidence: 99%